Post Pandemic Learning Culture : Which is Your Choice? - Mulyani, Sri; Irawan, Ade; Rosida, Siti Ayu (Universitas Pahlawan Tuanku Tambusai, 2023)
The Covid-19 influenced the way we live the lives including those in educational sector. This paper seeks to find the habit of the students in the learning process as it is a kind of transition from offline classes-on line classes and off line classes. The quantitative descriptive research approach used in this study narrates the data in light of the respondents' responses and assigns pertinent meanings students from semester three through seven who have participated in both on line and off line learning activities serve as the study's subjects in order to reflect on variations in learning styles. Answers to surveys distributed to respondents via the Google form were used to collect the data. The researcher can infer from the research's findings that the students themselves may find some of the responses to be perplexing. For instance, when asked again, the majority of them preferred the face-to-face learning approach despite their initial claims that online learning was more flexible and provided sufficient knowledge. This demonstrates that, despite the widespread usage of a number of new habits in the form of Â on line platforms, face-to-face instruction is still the preferred method for them.Â The paper conclude that the Covid-19 pandemic can influence the way the students learn in which, in some occasions are positiveÂ